The Knowledge Characteristics Work Design; Analysis of Job Fit Influence on Role Performance - Indartono, Setyabudi; Chiou, Hawjeng; Chen, Chun-Hsi Vivian (Journal of Human Capital, 2008)
This paperinvestigates how work design predicted Performance mediated by personal job Fit. This Study also explored difference of servant Leadership style moderate the model. 407 teachers from several schools in Indonesia were examined. The result indicates personal job fit mediate information processes ofknowledge characteristics related to /n role performance. Servant leadership moderate the relationship between knowledge characteristics and personal job fit, and moderate the relationship between personal job fit and in role performance. Servant leadership also found moderate these two relationships, differently. Implication of the findings for organizations and suggestions for future research are discussed. Keywords: Knowledge characteristics, personal Fit, intra Role Performance, Servant Leadership